Mental Illness, Mass Shootings, and the Future of Psychiatric Research into American Gun Violence - Metzl, Jonathan M. (Harv Rev Psychiatry, 2021)
This article outlines a four-part strategy for future research in mental health and complementary disciplines that will broaden understanding of mass shootings and multi-victim gun homicides. First, researchers must abandon the starting assumption that acts of mass violence are driven primarily by diagnosable psychopathology in isolated “lone wolf” individuals. The destructive motivations must be situated, instead, within larger social structures and cultural scripts. Second, mental health professionals and scholars must carefully scrutinize any apparent correlation of violence with mental illness for evidence of racial bias in the official systems that define, measure, and record psychiatric diagnoses, as well as those that enforce laws and impose criminal justice sanctions. Third, to better understand the role of firearm access in the occurrence and lethality of mass shootings, research should be guided by an overarching framework that incorporates social, cultural, legal, and political, but also psychological, aspects of private gun ownership in the United States. Fourth, effective policies and interventions to reduce the incidence of mass shootings over time—and to prevent serious acts of violence more generally—will require an expanded body of well-funded interdisciplinary research that is informed and implemented through the sustained engagement of researchers with affected communities and other stakeholders in gun violence prevention. Emerging evidence that the coronavirus pandemic has produced a sharp increase both in civilian gun sales and in the social and psychological determinants of injurious behavior adds special urgency to this agenda.